Exploring the Binding Interactions of Structurally Diverse dichalcogenoimidodiphosphinate Ligands with α-amylase: Spectroscopic Approach Coupled with Molecular Docking - Oyetunde, Temidayo (Elsevier, 2020)
Postprandial hyperglycemia has orchestrated untimely death among diabetic patients over the decades and regulation of α-amylase activity is now becoming a promising management option for type 2 diabetes. The present study investigated the binding interactions of three structurally diverse dichalcogenoimidodiphosphinate ligands with α-amylase to ascertain the affinity of the ligands for α-amylase using spectroscopic and molecular docking methods. The ligands were characterized using 1H and 31P NMR spectroscopy and CHN analysis. Diselenoimidodiphosphinate ligand (DY300), dithioimidodiphosphinate ligand (DY301), and thioselenoimidodiphosphinate ligand (DY302) quenched the intrinsic fluorescence intensity of α-amylase via a static quenching mechanism with bimolecular quenching constant (Kq) values in the order of x1011 M-1s-1, indicating formation of enzyme-ligand complexes. A binding stoichiometry of n≈1 was observed for α-amylase, with high binding constants (Ka). α-Amylase inhibition was as follow: Acarbose > DY301>DY300>DY302. Values of thermodynamic parameters obtained at temperatures investigated (298, 304 and 310 K) revealed spontaneous complex formation (ΔG<0) between the ligands and α-amylase; the main driving forces were hydrophobic interactions (with DY300, DY301, except DY302). UV–visible spectroscopy and F¨orster resonance energy transfer (FRET) affirmed change in enzyme conformation and binding occurrence. Molecular docking revealed ligands interaction with α-amylase via some key catalytic site amino acid residues (Asp197, Glu233 and Asp300). DY301 perhaps showed highest α-amylase inhibition (IC50, 268.11 ± 0.74 μM) due to its moderately high affinity and composition of two sulphide bonds unlike the others. This study might provide theoretical basis for development of novel α-amylase inhibitors from dichalcogenoimidodiphosphinate ligands for management of postprandial hyperglycemia.
Keywords: Anti-diabetic agents; Hyperglycemia; Spectroscopy; Ligand-protein binding; α-Amylase inhibition